QUENCHING OF EXCITED ATOMS BY COLLISIONS WITH STABLE MOLECULES - Bottcher, C; Sukumar, C (1977)
The authors are concerned with relatively simple semi-empirical models for quenching of excited atoms by stable molecules, i.e. the transfer of electronic energy into vibrational and translational degrees of freedom. The most notable example is the quenching for Na(33P) to the ground state by N 2. The cross sections are first related to those for free-electron-molecule scattering in a 'first-order' theory and it is shown that this simple theory leads to numerical values which are far too small. Thus the authors invoke an ionic collision complex formed by partial charge transfer and succeed in obtaining reasonable total cross sections and final-state branching ratios from a hybrid theory. Calculations are carried out for excited Li, Na and K colliding with H2, N2 and O2.